Tea Trade Dynamics: Assessing India’s Competitiveness in the Global Scenario using analytical tools RCA and SRCA - Ilias Hussain , Dr. Mushtaq Ahmad Shah, Bandna, Dr. Nitin Gupta, Muzahid Hussain (South Eastern European Journal of Public Health, 2025)
India,a pivotal player within the global agricultural landscape, derives considerable economic value from its tea industry, which occupies a critical position in both rural employment and foreign exchange earnings. While tea production has shown steady annual growth, export expansion has lagged, constrained by a complex interplay of factors. This study highlights the significance of tea as a crucial agricultural product for India, contributing to rural employment and foreign exchange earnings. Rising domestic consumption, formidable competition from established tea-exporting nations such as China, Sri Lanka, and Kenya, and the emergence of newer market entrants like Vietnam, the United Kingdom, Japan, Indonesia, and Nepal, collectively exert pressure on India's export share. This study seeks to evaluate the global competitive standing of India's tea industry by applying the Balassa Revealed Comparative Advantage(RCA) andSymmetrical Revealed Comparative Advantage (SRCA) indices,providing a nuanced insight into India's relative positioning. Results underscore that, despite intensified global competition, India’s tea industry retains substantial, under-leveraged potential to scale its global presence. This study suggests policy interventions and sustainable practices to ensure the long-term viability of the tea sector.